Analisis Kontribusi Perempuan Dalam Membantu Perekonomian Keluarga: ( Studi Pedagang Perempuan di Pasar Aurduri Kota Jambi ) - Bima Afandy Daulay; Elyanti Rosmanidar; Agusriandi Agusriandi (Jurnal Manajemen Riset Inovasi, 2024)
This research aims to find out what factors cause more women to sell at Aurduri market compared to men, to find out how women contribute to helping their family's economy at Aurduri market, and to find out what problems or obstacles female traders face when contributing to Aurduri market. . This research uses a qualitative method, with a total of 9 informants. The data sources used are primary and secondary data sources with data collection techniques through observation interviews and documentation. The results of the research show that there are three factors that cause more women to sell at the Aurduri market, namely: first, family economic factors, where the husband's income is not sufficient for daily living needs, and the costs of school children. The second factor is education and age, where female traders who have low education and are quite old and do not have the qualifications to work in other places, because they are old, but they are still fit and productive to work, decide to become traders at the Aurduri market. The third factor of self-actualization, the results of the research, showed that respondents admitted that they enjoyed selling at the market because apart from being able to meet friends, filling their free time also increased their income. The contribution of women traders to the family is classified as medium to high, which can be seen from the results of their sales which are used for daily needs, to increase family income, and also to save on unexpected costs. There are two obstacles faced by women traders, namely the weather conditions when it rains making buyers in the market lonely, secondly, the large number of home-scale vegetable sellers competes with the price and completeness of goods which are almost available in every neighborhood and housing complex, especially those on the road to the market. Aurduri makes buyers prefer shopping in nearby places.